Method for improving carbon fiber and aluminum-based resin composite material by utilizing temperature regulation and control
By introducing multifunctional nanomaterials and multi-stage phase change materials, combined with ultrasonic assistive technology and shape memory polymer layer, the problems of unstable performance and limited conductivity improvement of composite materials in the prior art are solved, and the high performance and durability of composite materials are achieved.
Patent Information
- Application Number
- CN202411325085.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has limitations in improving the performance of carbon fiber and aluminum-based resin composite materials, including the inability to cover multiple key temperature intervals during the entire curing process, the material performance is unstable at extreme temperatures, limited conductivity improvement, and the failure to fully utilize nanotechnology to optimize the performance of the interface layer.
By introducing multifunctional nanomaterials and multi-stage phase change materials, a multifunctional interface layer and a self-temperature control resin system are formed, and ultrasonic assistive technology and shape memory polymer layer are used to finely control the curing temperature and pressure to optimize the flowability and permeability of the resin.
The conductivity, mechanical strength and thermal stability of the composite material are significantly improved, ensuring the performance stability and durability of the material under extreme temperature and stress conditions, making it more suitable for high-performance applications.
Smart Images

Figure CN119502482A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a method for improving a carbon fiber and aluminum-based resin composite material by temperature control. Background Art
[0002] In modern materials science, the method of improving carbon fiber and aluminum-based resin composites by temperature control has been widely studied and applied. Such methods usually involve precise control of the temperature during the curing process of the composite material to improve the mechanical properties and thermal stability of the material. By controlling the curing temperature, the polymerization reaction of the resin can be optimized, thereby improving the internal microstructure and overall performance of the composite material.
[0003] One existing method involves using temperature-sensitive additives or phase change materials to adjust the curing environment and rate of the resin during the preparation of the composite material. For example, by adding microcapsule-type phase change materials, these materials release or absorb heat when a specific temperature is reached, thereby automatically adjusting the internal temperature during the curing process. This method can effectively prevent the accumulation of internal stress caused by too fast a curing rate, and improve the structural integrity and thermal stability of the composite material.
[0004] Although existing technologies have improved the performance of composite materials to a certain extent, there are still some obvious limitations. First, the application of a single phase change material usually cannot cover multiple critical temperature ranges throughout the curing process, resulting in unstable material properties at extreme temperatures. Secondly, the temperature control methods in existing technologies often cannot significantly improve the electrical conductivity of the material, limiting its application in the electronics industry. Finally, existing methods fail to make full use of nanotechnology to optimize the performance of the interface layer, thereby failing to maximize the mechanical properties and durability of composite materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for improving carbon fiber and aluminum-based resin composite materials by temperature control. The present invention significantly improves the electrical conductivity, mechanical strength and thermal stability of carbon fiber and aluminum-based resin composite materials by introducing multifunctional nanomaterials and multi-level phase change materials, thereby ensuring the performance stability and durability of the material under extreme temperature and stress conditions, making it more suitable for high-performance applications.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for improving carbon fiber and aluminum-based resin composite materials by temperature control, comprising the following steps:
[0007] S1. Forming a multifunctional interface layer on the surface of carbon fiber and aluminum-based materials, the interface layer enhances the interface bonding force through the combination of multiple nanomaterials and layered structure;
[0008] S2, resin impregnation using a self-regulating resin system containing temperature-sensitive microcapsules, which automatically adjusts the curing temperature and pressure within a specific temperature range;
[0009] S3. During the curing process, multi-stage phase change materials are used to regulate the internal temperature distribution through thermal response behaviors at different temperature stages;
[0010] S4, optimize the fluidity and permeability of resin through ultrasound-assisted technology;
[0011] S5. Utilize a thermally responsive polymer layer with shape memory function to automatically adjust the shape of the inner wall of the mold according to temperature changes to ensure the molding quality and structural integrity of the composite material.
[0012] Preferably, the S1 comprises:
[0013] Multifunctional nano-coatings were prepared by mixing carbon nanotubes, graphene and nano-silicon sheets;
[0014] The nano coating is evenly applied to the surface of carbon fiber and aluminum-based materials by solution dipping and spraying;
[0015] Drying and curing the coating material to form a high-strength bonding interface of the nanomaterial layer;
[0016] Further heat treatment is performed to optimize the microstructure and mechanical properties of the interface layer.
[0017] Preferably, S2 includes:
[0018] Introducing temperature-sensitive microcapsules into the resin, which contain ingredients that can release temperature-regulating substances;
[0019] The self-temperature regulating resin system is applied to the impregnation process of carbon fiber and aluminum-based materials;
[0020] After impregnation is completed, a heat treatment is applied at a temperature ranging from 100°C to 160°C to activate the microcapsules so that they automatically adjust the resin curing temperature;
[0021] According to the curing state of the resin, the heat treatment temperature and time are dynamically adjusted to ensure uniform curing of the resin.
[0022] Preferably, S3 includes:
[0023] Introducing multi-level phase change materials into composite materials, the phase change materials have different melting points and thermal response characteristics;
[0024] During the curing process, the ambient temperature is controlled to rise gradually, so that each level of phase change material undergoes phase change in sequence to absorb and release heat;
[0025] After the temperature of each stage is stabilized, it is maintained for a certain period of time to ensure that the internal temperature of the composite material is evenly distributed;
[0026] Finally, the phase change material is stably solidified through cooling treatment to lock the internal structure.
[0027] Preferably, S4 includes:
[0028] Ultrasonic treatment of the resin is performed using ultrasonic equipment with a frequency range of 20kHz to 50kHz;
[0029] Introducing vibration-sensitive additives into the resin, which improve the fluidity and permeability of the resin under ultrasonic excitation;
[0030] During resin impregnation, ultrasound is continuously used to reduce bubble formation and improve inter-fiber filling efficiency;
[0031] After impregnation is completed, stop the ultrasonic treatment and proceed to the next curing process.
[0032] Preferably, the S4 further comprises:
[0033] Adjust the frequency of the ultrasonic equipment to between 25kHz and 40kHz to adapt to the viscosity and flow characteristics of different resins;
[0034] According to the resin impregnation depth and the thickness of the composite material, set the ultrasonic power within the range of 200W to 400W;
[0035] During the ultrasonic treatment, the fluidity and penetration status of the resin are monitored in real time, and the frequency and power are appropriately adjusted through the feedback control system to ensure the best impregnation effect.
[0036] Preferably, S5 includes:
[0037] Applying a shape memory polymer layer to the inner wall of the mold, which can change shape within a certain temperature range;
[0038] During the curing process, as the temperature changes, the polymer layer automatically adjusts the shape of the inner wall of the mold to adapt to the changes in the composite material;
[0039] After curing is completed, the polymer layer is restored to its original state by cooling, and the finished product is removed from the mold;
[0040] The finished product is further heat treated to eliminate the internal stress that may be caused by the adjustment of the mold shape.
[0041] Preferably, the shape memory polymer layer comprises:
[0042] The activation temperature range of the shape memory polymer layer is selected to be 90°C to 180°C;
[0043] Adjusting the thickness of the shape memory polymer layer to ensure that it provides sufficient stress resistance during deformation, wherein the thickness ranges from 0.1 mm to 2 mm;
[0044] During the mold manufacturing process, the shape memory polymer layer is tightly combined with the mold main material to ensure that it functions stably throughout the entire curing process.
[0045] Preferably, the nanomaterials of the multifunctional interface layer include:
[0046] Carbon nanotubes, with a particle size range of 1 nanometer to 50 nanometers, are used to enhance the mechanical strength of the interface layer;
[0047] Graphene, with a thickness ranging from 0.34 nanometers to 10 nanometers, is used to improve the conductivity of the interface layer;
[0048] Nano silicon wafers, with a particle size ranging from 5 nanometers to 100 nanometers, are used to improve the thermal stability of the interface layer.
[0049] Preferably, S3 further comprises:
[0050] First, the first-stage phase change material is activated by setting the ambient temperature to 35°C to 45°C;
[0051] Then the temperature is gradually raised to 55℃~65℃, triggering the phase change of the second stage phase change material;
[0052] Finally, the temperature is raised to 75°C to 85°C to allow the third-stage phase change material to complete the phase change process and ensure the gradient control of the internal temperature.
[0053] The invention provides a method for improving a carbon fiber and aluminum-based resin composite material by utilizing temperature control.
[0054] It has the following beneficial effects:
[0055] 1. The present invention significantly improves the conductivity of the carbon fiber and aluminum-based resin composite material by introducing graphene and metal nanoparticles into the interface layer. This improvement makes the composite material suitable for high-performance electronic devices, improves electromagnetic shielding efficiency and electronic signal transmission capabilities, and is particularly suitable for application scenarios that require excellent electrical properties.
[0056] 2. The present invention introduces carbon nanotubes, graphene and nano silicon sheets into the interface layer, so that the composite material exhibits excellent mechanical strength and enhanced wear resistance. This makes the material not only exhibit higher tensile, compressive and bending resistance in high-load applications, but also exhibit better stability and reliability in long-term use.
[0057] 3. The present invention optimizes the curing process by using multi-stage phase change materials, so that the composite material can maintain more stable performance when experiencing high temperature operating environments. This thermal management strategy effectively controls the temperature gradient inside the material, reduces thermal stress, and improves the reliability and durability of the material under extreme temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0059] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for improving a carbon fiber and aluminum-based resin composite material by temperature control, comprising the following steps:
[0061] S1. A multifunctional interface layer is formed on the surface of carbon fiber and aluminum-based materials. This interface layer enhances the interface bonding force through the combination and layered structure of multiple nanomaterials. Through the superposition and interaction of these nanomaterials, it not only enhances the bonding force between carbon fiber and aluminum-based resin, but also optimizes the overall performance of the composite material. This multifunctional interface layer significantly improves the mechanical properties and thermal stability of the composite material, while also optimizing the electrical properties, making the composite material suitable for a wider range of industrial applications;
[0062] S2. Use a self-regulating resin system containing temperature-sensitive microcapsules for resin impregnation. The system automatically adjusts the curing temperature and pressure within a specific temperature range. Temperature-sensitive microcapsules are embedded in the resin system, and these microcapsules can release thermoregulating substances when a specific temperature is reached. When impregnating carbon fiber and aluminum-based materials, this self-regulating resin system can automatically adjust its curing rate and internal pressure according to the temperature changes during the curing process, thereby optimizing the fluidity and final physical properties of the resin. By adaptively adjusting the curing environment, this step significantly improves the uniformity of material curing, reduces the generation of internal stress and defects, and improves the quality and performance of the finished product;
[0063] S3. During the curing process, multi-stage phase change materials are used to regulate the internal temperature distribution through thermal response behaviors at different temperature stages. These materials have different phase change points at different temperature stages and can effectively absorb or release heat to regulate the temperature of the internal environment. By finely controlling the temperature, the microstructure of the material can be optimized and the thermal stress caused by uneven temperature can be reduced, thereby making the internal structure of the composite material more uniform, improving the mechanical properties and thermal stability of the material, especially in applications subjected to high temperatures or changing environments;
[0064] S4. Optimize the fluidity and permeability of the resin through ultrasonic-assisted technology. By adjusting the frequency and intensity of ultrasound, the vibration-sensitive additives in the resin can be activated, thereby enhancing the fluidity of the resin and its ability to penetrate carbon fibers. This technology significantly improves the impregnation effect of the resin, ensures the uniform distribution of fibers in the composite material, reduces voids and unimpregnated areas, and thus improves the overall performance and durability of the composite material;
[0065] S5. Using a thermoresponsive polymer layer with shape memory function, the shape of the inner wall of the mold is automatically adjusted according to temperature changes to ensure the molding quality and structural integrity of the composite material. This material can automatically change shape according to temperature changes. This allows the mold to dynamically adjust according to the expansion or contraction of the composite material during the curing process to meet the needs of different shapes and sizes. This improves the accuracy and quality of composite molding, making the molded product have better dimensional stability and surface smoothness, and reducing the need for post-processing.
[0066] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S1 includes:
[0067] The multifunctional nano-coating is prepared by mixing carbon nanotubes, graphene and nano-silicon wafers. The carbon nanotubes and graphene provide structural strength and electrical conductivity paths, while the nano-silicon wafers increase the thermal stability of the material through their high melting point. The mixed solution is treated with ultrasound to ensure uniform dispersion of the nanomaterials. The multifunctional nano-coating significantly enhances the tensile strength, bending strength and impact toughness of the composite material, not only improving the interface performance of the carbon fiber and aluminum-based materials, but also greatly improving the overall performance and reliability of the composite material.
[0068] The nano coating is evenly applied to the surface of carbon fiber and aluminum-based materials by solution dipping and spraying. During the dipping process, the material is completely immersed in the nano coating solution to ensure that every microscopic surface is covered; spraying is used for more precise and uniform coating distribution. This method can ensure uniform distribution of the nano coating and maximize surface coverage, thereby effectively improving the interfacial bonding strength and overall material consistency;
[0069] Drying and curing the coating material to form a high-strength bonding interface with the nanomaterial layer. The drying and curing steps enhance the structural integrity and interfacial bonding by expelling the solvent in the coating and promoting chemical cross-linking between the nanomaterials, and form a strong and durable interface with the nanocoating, which greatly improves the durability and performance stability of the material;
[0070] After initial drying and curing, further heat treatment is applied to optimize the microstructure and mechanical properties of the nanocoating through further heat treatment to optimize the microstructure and mechanical properties of the interface layer. The heat treatment at this stage significantly improves the mechanical strength and environmental resistance of the interface layer, ensuring the high performance and reliability of the composite material under extreme conditions.
[0071] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S2 includes:
[0072] Temperature-sensitive microcapsules are introduced into the resin. The microcapsules contain ingredients that can release temperature-regulating substances. When the trigger temperature is reached, the shell of the microcapsule breaks and releases the internal substances. These substances can quickly adjust the temperature of the resin and speed up or slow down the curing reaction. The introduction of temperature-sensitive microcapsules can accurately control the curing process of the resin and improve the quality and performance of the finished product. Especially in the manufacture of complex parts, it can effectively reduce defects caused by uneven curing.
[0073] The self-temperature regulating resin system is applied to the impregnation process of carbon fiber and aluminum-based materials, and the resin system containing microcapsules is applied to the impregnation treatment of carbon fiber and aluminum-based materials. By dipping or rolling, the resin is evenly coated on each part of the material to achieve the best composite effect, thereby ensuring the uniform distribution and consistent curing of the resin in the composite material, reducing the internal stress and defects caused by improper curing, and enhancing the overall performance and reliability of the product;
[0074] After impregnation, heat treatment at a temperature range of 100°C to 160°C is applied to activate the microcapsules so that they automatically adjust the resin curing temperature. The purpose of this step is to activate the microcapsules in the resin, rupture them and release the temperature-regulating chemicals contained therein. This heat treatment step makes the curing of the composite material more uniform, reduces the variation of physical properties caused by temperature fluctuations, and improves the strength and environmental resistance of the product.
[0075] According to the curing state of the resin, the heat treatment temperature and time are dynamically adjusted to ensure uniform curing of the resin. Dynamic adjustment allows real-time optimization of the curing process, adapts to changes in the material during the curing process, and ensures the quality and consistency of the final product. This dynamic adjustment strategy maximizes the flexibility of the manufacturing process and product quality, while significantly reducing scrap rates and improving economic benefits.
[0076] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S3 includes:
[0077] Introducing multi-level phase change materials into composite materials, which have different melting points and thermal response characteristics. Phase change materials can absorb a large amount of heat energy when reaching their melting point or release heat energy during the cooling process. Through this heat energy exchange, phase change materials can effectively control the temperature of composite materials, prevent the curing behavior of resins from being affected by excessively high or low temperatures, and make the temperature of composite materials more stable during the curing process, avoiding local overheating or overcooling, thereby improving the quality and performance consistency of composite materials;
[0078] During the curing process, the ambient temperature is controlled to rise gradually, so that each level of phase change material undergoes phase change in sequence to absorb and release heat. During the curing process, the ambient temperature is gradually increased through external heating equipment, and phase change materials with different melting points undergo phase change in sequence according to the set program. As the temperature gradually rises, the low-melting-point phase change material undergoes phase change first to absorb heat, followed by the medium and high-melting-point materials. This hierarchical control can finely adjust the internal temperature and optimize the curing environment of the resin. By precisely controlling the timing and duration of the phase change material, the thermal stability of the composite material during the curing process can be significantly improved, and the generation of thermal stress and defects can be reduced, thereby improving the mechanical properties and durability of the final product;
[0079] After the temperature of each stage is stable, it is kept for a certain period of time to ensure that the internal temperature of the composite material is evenly distributed. After each phase change stage, the ambient temperature is kept for a certain period of time to ensure that the temperature inside the composite material is completely stable and evenly distributed. This method can ensure that the degree of curing of each part of the composite material is consistent, greatly improving the overall performance and structural integrity of the material;
[0080] Finally, through cooling treatment, the phase change material is stably solidified and the internal structure is locked. Slow cooling allows the phase change material to re-solidify in a controlled manner. The heat released in this process can be evenly absorbed by the resin, avoiding internal stress and structural unevenness that may be caused by rapid cooling. It can be stable under lower stress, enhancing the dimensional stability of the material and reliability of long-term use.
[0081] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S4 includes:
[0082] Use ultrasonic equipment with a frequency range of 20kHz to 50kHz to treat the resin. The vibration of the ultrasonic wave can break the intermolecular force in the resin, reduce its viscosity, and thus increase fluidity. At the same time, it can significantly improve the wettability and impregnation effect of the resin, ensuring that the resin can be evenly distributed at every contact point between the carbon fiber and the aluminum material, thereby improving the structural integrity and mechanical strength of the composite material;
[0083] Introducing vibration-sensitive additives into the resin, these additives improve the fluidity and permeability of the resin under ultrasonic excitation. When ultrasonic waves act on the resin containing these additives, the additives change due to vibration, such as the vibration of microbubbles causing them to rupture or deform, thereby further reducing the local viscosity and surface tension of the resin. The use of these vibration-sensitive additives further enhances the fluidity and permeability of the resin, making it easier for the resin to fill the fine structure of carbon fibers, reducing the formation of bubbles and voids, and improving the mechanical properties and durability of the composite material;
[0084] During resin impregnation, ultrasound is continuously used to reduce bubble formation and improve inter-fiber filling efficiency. This method effectively reduces bubble formation and accumulation. Reducing bubbles ensures that the composite material has higher density and uniformity.
[0085] After impregnation, the ultrasonic treatment is stopped and the next step of curing is entered. The purpose of stopping the ultrasonic treatment is to maintain the stability of the internal structure of the resin so that it is not affected by external vibrations during the curing process, thereby avoiding the formation of new bubbles or material movement, ensuring that the resin can maintain its optimized state during curing, thereby improving the structural integrity and performance of the final composite material.
[0086] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S4 further comprises:
[0087] Adjust the frequency of the ultrasonic equipment to between 25kHz and 40kHz to adapt to the viscosity and flow characteristics of different resins. The adjustment of the ultrasonic frequency can change the penetration depth and intensity of the vibration wave, thereby affecting the fluidity of the resin to varying degrees. Higher frequency ultrasound is suitable for low-viscosity resins, while lower frequency is more suitable for high-viscosity resins, which helps to improve their fluidity and wettability, ensuring that the resin can achieve the best penetration effect in every part of the composite material, thereby improving the uniformity and overall performance of the composite material;
[0088] According to the resin impregnation depth and the thickness of the composite material, the ultrasonic power is set within the range of 200W to 400W. The power adjustment affects the energy output of the ultrasonic wave. High power can accelerate the flow and penetration of the resin, especially in thick or dense composite material structures. This range of power ensures that the ultrasonic wave can fully penetrate the material without causing local overheating or resin degradation, thereby effectively reducing the generation of bubbles and unwetted areas, and improving the mechanical strength and environmental resistance of the product.
[0089] During the ultrasonic treatment process, the fluidity and penetration state of the resin are monitored in real time, and the frequency and power are appropriately adjusted through the feedback control system to ensure the best impregnation effect. The feedback control system can dynamically adjust the processing parameters in response to the real-time state changes of the material. This control strategy ensures the flexibility and accuracy of the treatment process, allowing instant adjustments to respond to unexpected changes in material behavior. Through real-time monitoring and automatic adjustment, the optimization of the ultrasonic treatment process is ensured, the processing efficiency and quality are improved, and the production quality of the composite materials is improved, and the variation and defects in production are reduced, thereby improving the reliability and economy of the overall production.
[0090] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S5 includes:
[0091] Apply a shape memory polymer layer on the inner wall of the mold, which can change shape within a certain temperature range. Shape memory polymers have unique thermal sensing properties. They can soften when heated and deform according to the previously "memorized" shape. When cooled, they can return to their original shape. The mold using shape memory polymers can accurately match the expansion or contraction of the composite material during the curing process, thereby ensuring that the finished product has higher dimensional accuracy and surface finish, reducing the need for post-processing;
[0092] During the curing process, as the temperature changes, the polymer layer automatically adjusts the shape of the inner wall of the mold to adapt to the changes in the composite material. The thermal response action of the shape memory polymer enables the inner wall of the mold to dynamically adjust and fill the gaps that may be caused by the volume change of the material caused by the chemical reaction, thereby reducing the internal stress and defects caused by the shrinkage or expansion of the curing, and improving the mechanical strength and long-term stability of the finished product;
[0093] After curing is completed, the polymer layer is restored to its original state by cooling, and the finished product is taken out of the mold. The restoring force of the shape memory polymer ensures that the mold can restore its original shape after use, which facilitates the removal of the finished product without damaging its surface or structure, thereby reducing possible mechanical damage to the finished product and maintaining its integrity and aesthetics;
[0094] The finished product removed from the mold undergoes further heat treatment to eliminate any internal stress that may be introduced during the mold shape adjustment process, thereby improving the structural stability and durability of the finished product and ensuring that the product can perform better in actual applications, especially when subjected to mechanical loads and environmental stresses.
[0095] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the shape memory polymer layer comprises:
[0096] The activation temperature range of the shape memory polymer layer is selected to be 90°C to 180°C. This temperature range is based on the temperatures typically reached during the resin curing process to ensure that the SMP can effectively respond to temperature changes throughout the curing cycle and ensure that the polymer can work effectively throughout the curing cycle;
[0097] Adjust the thickness of the shape memory polymer layer to ensure that it provides sufficient stress resistance during deformation. The thickness ranges from 0.1 mm to 2 mm. This thickness can balance deformation performance and structural integrity, ensuring that the volume change of the material can be effectively adapted without sacrificing the durability and reusability of the mold. By adjusting the thickness of the polymer layer, its mechanical and thermal response behavior can be optimized, the adaptability of the mold and the controllability of the production process can be improved, and the defect rate in the manufacture of composite materials can be reduced;
[0098] In the mold manufacturing process, the shape memory polymer layer is tightly combined with the main material of the mold to ensure that it functions stably throughout the curing process. The shape memory polymer layer is firmly fixed inside the mold to avoid position shifting or falling off at high temperatures or during repeated use. This stable combination ensures that the function of the polymer layer is not disturbed during the curing process, which not only ensures its reliability and effectiveness during the curing process, but also enhances the overall durability of the mold and the consistency of multiple uses, thereby improving production efficiency and reducing maintenance costs.
[0099] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the nanomaterial of the multifunctional interface layer comprises:
[0100] Carbon nanotubes, with a particle size range of 1 nanometer to 50 nanometers, are used to enhance the mechanical strength of the interface layer. Carbon nanotubes have extremely high tensile strength and modulus due to their unique tubular structure and strong covalent bonds of carbon atoms. When they are evenly distributed in the matrix of the composite material, they can significantly improve the material's tensile, bending and impact resistance. The addition of carbon nanotubes not only significantly improves the mechanical strength of the composite material, but also enhances its wear resistance and durability, making the material suitable for more demanding application environments;
[0101] Graphene, with a thickness ranging from 0.34 nanometers to 10 nanometers, is used to improve the conductivity of the interface layer. The two-dimensional structure and high surface area of graphene enable it to form a continuous conductive network in the composite material, greatly improving the electrical conductivity of the material. In addition, the introduction of graphene can also improve thermal conductivity, which helps the thermal management of the material in high-power applications;
[0102] Nano silicon wafers, with a particle size range of 5 nanometers to 100 nanometers, are used to improve the thermal stability of the interface layer. Due to their good thermal stability and low thermal expansion coefficient, nano silicon wafers can maintain the structural stability of the material under high temperature environments. After the introduction of nano silicon wafers, the thermal stability of the composite material is significantly improved, and it is suitable for high-temperature applications such as engine components or other hot environments. At the same time, the presence of nano silicon wafers also enhances the overall thermal shock resistance and long-term stability of the material.
[0103] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, S3 further comprises:
[0104] First, the first-stage phase change material is activated by setting the ambient temperature to 35°C to 45°C. These materials are usually designed to begin absorbing heat within this temperature range to slow down the initial curing reaction and avoid internal stress caused by the heat generated by the rapid reaction. This method can effectively control the initial curing temperature and avoid rapid or uneven curing of the material due to excessive temperature, thereby improving the quality and consistency of the composite material.
[0105] Then the temperature is gradually raised to 55℃~65℃, triggering the phase change of the second-stage phase change material. The phase change material in this stage is designed to release the previously absorbed heat within this temperature range, and continue to control the curing speed and heat distribution. Through the temperature control of the second stage, the heat distribution inside the material can be further refined, the curing process can be optimized, the defects caused by temperature fluctuations can be reduced, and the structural integrity of the final product can be improved;
[0106] Finally, the temperature is raised to 75℃~85℃ to complete the phase change process of the third-stage phase change material and ensure the gradient control of the internal temperature. At this stage, the phase change material stably releases heat at high temperature to support the complete curing of the material and ensure uniform temperature throughout the curing process. The temperature control at this stage ensures that the composite material can be evenly chemically cross-linked in the final stage of curing, enhancing the mechanical properties and durability of the material and ensuring that the finished product has excellent physical and chemical properties.
[0107] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.
[0108] Example 1: High-performance composites for aerospace applications
[0109] Implementation steps:
[0110] Interface layer preparation: A multifunctional interface layer containing carbon nanotubes, graphene and nano-silicon sheets is applied to the surface of carbon fiber and aluminum-based materials. High-precision spraying technology is used to ensure that the interface layer is evenly distributed.
[0111] Resin impregnation: Use a resin system containing temperature-sensitive microcapsules for impregnation. The microcapsules automatically adjust the curing rate of the resin during the curing process and optimize the curing conditions.
[0112] Curing control: The temperature of the curing environment is gradually controlled by multi-stage phase change materials, gradually rising from 35°C to 85°C to ensure uniform distribution of internal temperature.
[0113] Ultrasonic treatment: Ultrasonic technology (25kHz ~ 40kHz) is used during the resin curing process to reduce bubble formation and improve the filling efficiency between fibers.
[0114] Example 2: Lightweight composite materials for the automotive industry
[0115] Implementation steps:
[0116] Interface layer preparation: An interface layer containing trace amounts of multi-walled carbon nanotubes is created on the carbon fiber and aluminum alloy substrate to improve impact absorption performance.
[0117] Resin treatment: Select low-temperature fast-curing resin, and adjust the resin system containing microcapsules to cure within the range of 45°C to 65°C.
[0118] Mold adjustment: Use shape memory polymer as the inner layer of the mold to adapt to the volume changes of the composite material during the curing process.
[0119] Molding completed: Use the cooling system to accelerate the cooling process after molding to quickly remove the finished product from the mold.
[0120] Example 3: Conductive composite materials for the electronics industry
[0121] Implementation steps:
[0122] Interface layer optimization: Apply a conductive interface layer composed of graphene and nanosilver particles to the heat sink substrate of electronic products.
[0123] Resin optimization: Select highly conductive resins and add temperature-sensitive microcapsules to regulate the curing speed to ensure maximum conductivity.
[0124] Ultrasonic Application: Low power ultrasonic waves (20kHz) are applied during the curing process to maintain the integrity of the resin's internal structure and the uniformity of the conductive pathways.
[0125] Cooling and Curing: During the cool-down phase after curing, rapid cooling techniques are used to lock in the conductive paths in the resin.
[0126] Comparative experiment 1: Conductivity test experimental design
[0127] Experimental purpose: This comparative experiment aims to verify the improvement effect of the interface layer containing graphene and metal nanoparticles used in the present invention on the electrical conductivity of carbon fiber and aluminum-based resin composite materials.
[0128] Experimental setup and steps
[0129] Sample preparation
[0130] Experimental group: carbon fiber and aluminum-based resin composite material, the interface layer contains graphene and metal nanoparticles.
[0131] Control group A: pure carbon fiber and aluminum-based resin composite material without additives.
[0132] Control group B: composite material with only graphene in the interface layer.
[0133] Sample size: All samples were prepared to the same size, for example 100mmx10mmx1mm.
[0134] Conductivity measurement steps:
[0135] Equipment preparation: Use the four-point probe method and the corresponding conductivity tester;
[0136] Environmental settings: Ensure that all tests are performed at room temperature (about 25°C) and standard atmospheric pressure.
[0137] Test execution:
[0138] Place the probe evenly on the sample surface;
[0139] The current through the sample and the corresponding voltage are recorded.
[0140] Data recording: Each sample was measured at least three times to ensure the accuracy and repeatability of the data.
[0141] The comparative experimental data are shown in Table 1:
[0142] Table 1 Conductivity test experimental data table
[0143]
[0144] From the data in Table 1, we can get:
[0145] The conductivity of the experimental group was significantly higher than that of the control group A and the control group B. The average conductivity of the experimental group was about 938 S / m, while the average conductivity of the control group A was about 186 S / m and the average conductivity of the control group B was about 471 S / m. This shows that the addition of the interface layer of graphene and metal nanoparticles significantly improves the conductivity of the composite material.
[0146] Comparative experiment 2: Mechanical properties comparison test
[0147] Experimental purpose: To evaluate the effect of the present invention on improving the mechanical properties of carbon fiber and aluminum-based resin composites.
[0148] Experimental setup and steps
[0149] Sample preparation
[0150] Experimental group: carbon fiber and aluminum-based resin composite materials, the interface layer contains carbon nanotubes, graphene and nano-silicon sheets.
[0151] Control group A: carbon fiber and aluminum-based resin composite material without any nano-reinforcement agent.
[0152] Control group B: a composite material containing only carbon nanotubes in the interface layer.
[0153] Sample size: All samples were prepared to the same size, for example 250mmx25mmx5mm.
[0154] Mechanical properties test steps:
[0155] Tensile test: Use a standard tensile testing machine in accordance with ASTMD3039;
[0156] Compression test: Use compression test machine according to ASTMD3410 standard;
[0157] Bending test: The three-point bending test equipment was used in accordance with ASTM D790.
[0158] Data Recording: Each sample was tested at least three times to ensure data accuracy and repeatability.
[0159] The comparative experimental data are shown in Table 2:
[0160] Table 2 Mechanical properties test experimental data table
[0161]
[0162] From the data in Table 2, we can get:
[0163] The experimental group showed significantly higher performance than the control group in the tensile strength test. The average calculated strength of the experimental group was about 838MPa, while the average calculated strength of the control group A was about 465MPa and the average calculated strength of the control group B was about 602MPa. This shows that the multifunctional interface layer containing carbon nanotubes, graphene and nano-silicon sheets significantly enhances the mechanical properties of the composite material, especially its tensile strength.
[0164] Comparative experiment 3: Thermal stability test
[0165] Experimental purpose: To verify the effect of the multi-stage phase change material used in the present invention on the thermal stability of carbon fiber and aluminum-based resin composite materials.
[0166] Experimental setup and steps
[0167] Sample preparation
[0168] Experimental group: Carbon fiber and aluminum-based resin composites using multi-stage phase change materials to optimize the curing process;
[0169] Control group A: carbon fiber and aluminum matrix resin composite with standard curing procedure, without phase change material;
[0170] Control group B: carbon fiber and aluminum-based resin composite material using a single phase change material.
[0171] Test Method
[0172] Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were used to test the thermal stability of the samples;
[0173] DSC test: measures the heat flow change of a material during heating to evaluate its heat capacity and phase change behavior;
[0174] TGA test: Gradually heat the sample to 600°C in a non-oxidizing environment and record the mass change of the material to evaluate its thermal decomposition behavior.
[0175] Data recording and analysis
[0176] Each sample was tested three times to ensure the reliability and repeatability of the results;
[0177] Record all important data including onset of decomposition temperature, temperature of maximum decomposition rate and residual mass
[0178] The comparative experimental data are shown in Table 3:
[0179] Table 3 Thermal stability test data record
[0180]
[0181]
[0182] From the data in Table 3, we can get:
[0183] The experimental group performed better than the control group A and the control group B in terms of thermal stability. The average initial decomposition temperature of the experimental group was 279°C, which was significantly higher than the average initial decomposition temperature of the control group A of 262°C and the control group B of 270°C. In addition, the maximum decomposition rate temperature of the experimental group was 452°C on average, which was also higher than the 432°C of the control group A and the 440°C of the control group B. The residual mass percentage of the experimental group was also higher than that of the control group. These results clearly show that the present invention significantly improves the thermal stability of the composite material by using a multi-stage phase change material, making it more suitable for application in high temperature environments.
[0184] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for improving carbon fiber and aluminum-based resin composite materials by temperature control, characterized in that: The following steps are involved: S1. Forming a multifunctional interface layer on the surface of carbon fiber and aluminum-based materials, the interface layer enhances the interface bonding force through the combination of multiple nanomaterials and layered structure; S2, resin impregnation using a self-regulating resin system containing temperature-sensitive microcapsules, which automatically adjusts the curing temperature and pressure within a specific temperature range; S3. During the curing process, multi-stage phase change materials are used to regulate the internal temperature distribution through thermal response behaviors at different temperature stages; S4, optimize the fluidity and permeability of resin through ultrasound-assisted technology; S5. Utilize a thermally responsive polymer layer with shape memory function to automatically adjust the shape of the inner wall of the mold according to temperature changes to ensure the molding quality and structural integrity of the composite material.
2. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: The S1 includes: Multifunctional nano-coatings were prepared by mixing carbon nanotubes, graphene and nano-silicon sheets; The nano coating is evenly applied to the surface of carbon fiber and aluminum-based materials by solution dipping and spraying; Drying and curing the coating material to form a high-strength bonding interface of the nanomaterial layer; Further heat treatment is performed to optimize the microstructure and mechanical properties of the interface layer.
3. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: The S2 includes: Introducing temperature-sensitive microcapsules into the resin, which contain ingredients that can release temperature-regulating substances; The self-temperature regulating resin system is applied to the impregnation process of carbon fiber and aluminum-based materials; After impregnation is completed, a heat treatment is applied at a temperature ranging from 100°C to 160°C to activate the microcapsules so that they automatically adjust the resin curing temperature; According to the curing state of the resin, the heat treatment temperature and time are dynamically adjusted to ensure uniform curing of the resin.
4. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: The S3 includes: Introducing multi-level phase change materials into composite materials, the phase change materials have different melting points and thermal response characteristics; During the curing process, the ambient temperature is controlled to rise gradually, so that each level of phase change material undergoes phase change in sequence to absorb and release heat; After the temperature of each stage is stabilized, it is maintained for a certain period of time to ensure that the internal temperature of the composite material is evenly distributed; Finally, the phase change material is stably solidified through cooling treatment to lock the internal structure.
5. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: The S4 includes: Ultrasonic treatment of the resin is performed using ultrasonic equipment with a frequency range of 20kHz to 50kHz; Introducing vibration-sensitive additives into the resin, which improve the fluidity and permeability of the resin under ultrasonic excitation; During resin impregnation, ultrasound is continuously used to reduce bubble formation and improve inter-fiber filling efficiency; After impregnation is completed, stop the ultrasonic treatment and proceed to the next curing process.
6. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 5, characterized in that: The S4 further comprises: Adjust the frequency of the ultrasonic equipment to between 25kHz and 40kHz to adapt to the viscosity and flow characteristics of different resins; According to the resin impregnation depth and the thickness of the composite material, set the ultrasonic power within the range of 200W to 400W; During the ultrasonic treatment, the fluidity and penetration status of the resin are monitored in real time, and the frequency and power are appropriately adjusted through the feedback control system to ensure the best impregnation effect.
7. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: The S5 includes: Applying a shape memory polymer layer to the inner wall of the mold, which can change shape within a certain temperature range; During the curing process, as the temperature changes, the polymer layer automatically adjusts the shape of the inner wall of the mold to adapt to the changes in the composite material; After curing is completed, the polymer layer is restored to its original state by cooling, and the finished product is removed from the mold; The finished product is further heat treated to eliminate the internal stress that may be caused by the adjustment of the mold shape.
8. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 7, characterized in that: The shape memory polymer layer comprises: The activation temperature range of the shape memory polymer layer is selected to be 90°C to 180°C; Adjusting the thickness of the shape memory polymer layer to ensure that it provides sufficient stress resistance during deformation, wherein the thickness ranges from 0.1 mm to 2 mm; During the mold manufacturing process, the shape memory polymer layer is tightly combined with the mold main material to ensure that it functions stably throughout the entire curing process.
9. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 1, characterized in that: Nanomaterials for the multifunctional interface layer include: Carbon nanotubes, with a particle size range of 1 nanometer to 50 nanometers, are used to enhance the mechanical strength of the interface layer; Graphene, with a thickness ranging from 0.34 nanometers to 10 nanometers, is used to improve the conductivity of the interface layer; Nano silicon wafers, with a particle size ranging from 5 nanometers to 100 nanometers, are used to improve the thermal stability of the interface layer.
10. The method for improving carbon fiber and aluminum-based resin composite materials by temperature control according to claim 4, characterized in that: The S3 further comprises: First, the first-stage phase change material is activated by setting the ambient temperature to 35°C to 45°C; Then the temperature is gradually raised to 55℃~65℃, triggering the phase change of the second stage phase change material; Finally, the temperature is raised to 75°C to 85°C to allow the third-stage phase change material to complete the phase change process and ensure the gradient control of the internal temperature.
Citation Information
Cited By
Synthetic latex polymerization reaction temperature optimization control method
CN120595892A
Thermal insulation material with fireproof and thermal insulation characteristics and manufacturing method thereof
CN120921766A
A heat-insulating material with fire-resistant and heat-insulating properties and its manufacturing method
CN120921766B